2021
DOI: 10.1186/s12883-021-02189-6
|View full text |Cite
|
Sign up to set email alerts
|

Increase of blood-brain barrier leakage is related to cognitive decline in vascular mild cognitive impairment

Abstract: Background Blood-brain barrier (BBB) breakdown, as an early biomarker for vascular mild cognitive impairment (vMCI), has only been validated by a few studies. The aim of this study was to investigate whether compromised BBB integrity is involved in vMCI patients, and detect the relationship between BBB breakdown and cognitive function. BBB leakage in vMCI was explored, and the relationship between BBB leakage and cognitive function was discussed in this study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
(52 reference statements)
0
31
0
Order By: Relevance
“…Vascular pathology in AD is an expanding subject and a growing number of studies show that vascular-related damage in the brain and retina can predict cognitive decline ( Vidal and Mavet, 1989 ; Baker et al, 2007 ; Gharbiya et al, 2014 ; Boyle et al, 2015 ; Bulut et al, 2016 , 2018 ; Cunha et al, 2017 ; McGrory et al, 2017 ; Planton et al, 2017 ; Cabrera DeBuc et al, 2018 ; Deal et al, 2018 ; Jiang et al, 2018 ; O’Bryhim et al, 2018 ; van der Flier et al, 2018 ; Iadecola et al, 2019 ; Jung et al, 2019 ; Montagne et al, 2020 ; Shi et al, 2020a ; Li et al, 2021 ). Cerebral vascular damage such as ischemia leads to disturbed nutrient supply, induces oxidative stress and inflammatory activities, impedes Aβ clearance and/or alters amyloid-processing enzymes ( Marchesi, 2011 ), all of which can contribute to neurodegeneration and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular pathology in AD is an expanding subject and a growing number of studies show that vascular-related damage in the brain and retina can predict cognitive decline ( Vidal and Mavet, 1989 ; Baker et al, 2007 ; Gharbiya et al, 2014 ; Boyle et al, 2015 ; Bulut et al, 2016 , 2018 ; Cunha et al, 2017 ; McGrory et al, 2017 ; Planton et al, 2017 ; Cabrera DeBuc et al, 2018 ; Deal et al, 2018 ; Jiang et al, 2018 ; O’Bryhim et al, 2018 ; van der Flier et al, 2018 ; Iadecola et al, 2019 ; Jung et al, 2019 ; Montagne et al, 2020 ; Shi et al, 2020a ; Li et al, 2021 ). Cerebral vascular damage such as ischemia leads to disturbed nutrient supply, induces oxidative stress and inflammatory activities, impedes Aβ clearance and/or alters amyloid-processing enzymes ( Marchesi, 2011 ), all of which can contribute to neurodegeneration and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Mooijaart and colleagues found an association between attention/executive function and systemic inflammatory biomarkers, but they did not find an association between working or episodic memory and inflammation [ 35 ]. Li and colleagues reported that patients diagnosed with mild vascular cognitive impairment showed diminished information processing speed, attention, executive function, spatial function, and language function but no measurable change in memory [ 36 ]. Hence, it may be that our healthy group of older people with the highest extracellular/intracellular water ratios, who performed poorer on the Flanker test of executive function and attention, are demonstrating early changes in cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology to the vascular system appears to be a primary path to impaired cognitive function. Leakage of blood plasma through the blood–brain barrier is believed to contribute to even mild cognitive impairment [ 36 ]. This leakage through the blood–brain barrier is measurable through imaging of the hippocampus of the brain and is tightly coupled with cognitive status [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have published extensively on BBB dysfunction in AD [ 92 , 93 , 94 , 95 , 96 ]. In addition, a long history of BBB dysfunction in ALS patients had been previously reviewed [ 97 ]; however, in the “modern era”, Garbuzova-Davis and colleagues at the University of South Florida began to study BBB integrity in transgenic SOD1 mice in the early 2000s, finding evidence of BBB and blood–spinal cord barrier (BSCB) dysfunction both in this ALS model as well as in patients with ALS [ 98 , 99 , 100 ].…”
Section: Par1 Apc and Neurodegenerationmentioning
confidence: 99%